Titin-truncating variants affect heart function in disease cohorts and the general population - Schafer, Sebastian; De Marvao, Antonio; Adami, Eleonora; Fiedler, Lorna R.; Ng, Benjamin; Khin, Ester; Rackham, Owen J. L.; Van Heesch, Sebastiaan; Pua, Chee J.; Kui, Miao; Walsh, Roddy; Tayal, Upasana; et al. (Nature Genetics, 2017)
Titin-truncating variants (TTNtv) commonly cause dilated cardiomyopathy (DCM). TTNtv are also encountered in 1/41% of the general population, where they may be silent, perhaps reflecting allelic factors. To better understand TTNtv, we integrated TTN allelic series, cardiac imaging and genomic data in humans and studied rat models with disparate TTNtv. In patients with DCM, TTNtv throughout titin were significantly associated with DCM. Ribosomal profiling in rat showed the translational footprint of premature stop codons in Ttn, TTNtv-position-independent nonsense-mediated degradation of the mutant allele and a signature of perturbed cardiac metabolism. Heart physiology in rats with TTNtv was unremarkable at baseline but became impaired during cardiac stress. In healthy humans, machine-learning-based analysis of high-resolution cardiac imaging showed TTNtv to be associated with eccentric cardiac remodeling. These data show that TTNtv have molecular and physiological effects on the heart across species, with a continuum of expressivity in health and disease.
CRIS-Team Scopus Importer:2023-03-08